State of the Art and Prospects in Metal-Organic Framework-Derived Microwave Absorption Materials - Ren, Shuning; Yu, Haojie; Wang, Li; Huang, Zhikun; Lin, Tengfei; Huang, Yudi; Yang, Jian; Hong, Yichuan; Liu, Jinyi (Nano-micro letters, 2022)
Highlights The metal organic frameworks derived microwave absorption materials (MOF derived MAMs) were systematically reviewed. The design principles, preparation methods and effect of microstructures and composites of MOF derived MAMs were discussed. The challenges and further research directions of MOF derived MAMs were presented Microwave has been widely used in many fields, including communication, medical treatment and military industry; however, the corresponding generated radiations have been novel hazardous sources of pollution threating human’s daily life. Therefore, designing high-performance microwave absorption materials (MAMs) has become an indispensable requirement. Recently, metal–organic frameworks (MOFs) have been considered as one of the most ideal precursor candidates of MAMs because of their tunable structure, high porosity and large specific surface area. Usually, MOF-derived MAMs exhibit excellent electrical conductivity, good magnetism and sufficient defects and interfaces, providing obvious merits in both impedance matching and microwave loss. In this review, the recent research progresses on MOF-derived MAMs were profoundly reviewed, including the categories of MOFs and MOF composites precursors, design principles, preparation methods and the relationship between mechanisms of microwave absorption and microstructures of MAMs. Finally, the current challenges and prospects for future opportunities of MOF-derived MAMs are also discussed.